Kajian Pembentukan Unit Layanan Pengadaan Barang/Jasa Pemerintah di Pemerintah Kota Bekasi - Adi Susila (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2012)
In a way to implement the rule from 14th and 130th section 1st section of Peraturan Presiden number 70 year 2012 which regional government have to shape Unit Layanan Pengadaan (ULP) before 2014, hence Bekasi Major with DPRD Kota Bekasi arrange Raperda about Kantor Layanan Pengadaan Barang/Jasa Kota Bekasi. Then, based on Perpres 70 2012 3rd section 1st, 2nd, 3rd, and 4th subsection, ULP is permanent, stand on its own side, or included in an existed unit. ULP may be put on a single structural unit that the making of it based on legislation rule which ruling government institution. Another way, ULP that belonging to the existed unit is integrated into the structural unit which functionally doing a task and function in the service and property provision sector. The set of ULP fixed associated with the needs that at least consist of functions as : Headmaster, Secretary, and Workgroup